Stem Cells: From Myth to Reality and Evolving - Haider, Khawaja Husnain (De Gruyter, 2019)
This book is a continuum of the first two books published in the STEM CELLS series entitled "Stem Cells: From Drug to Drug Discovery" and "Stem Cells: From Hype to Real Hope" which were published in 2017 and 2019, respectively. The scope of the book encompasses a wide range of topics with a latitude from adult stem cells to pluripotent stem cells in regenerative medicine either alone or as part of the combinatorial therapeutic intervention approach as "drug" besides their application as tools (disease model) during drug development process. Written by a leading group of researchers, the book encompasses experimental to clinical aspects of stem/progenitors cells, their biology, and characteristics.